If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + 21 = 15 Reorder the terms: 21 + 3m = 15 Solving 21 + 3m = 15 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 3m = 15 + -21 Combine like terms: 21 + -21 = 0 0 + 3m = 15 + -21 3m = 15 + -21 Combine like terms: 15 + -21 = -6 3m = -6 Divide each side by '3'. m = -2 Simplifying m = -2
| 3n+4=34 | | -2x+5+7x=55 | | 4(p+6)=8p | | x^3-6X^2-x+30=0 | | 11r-2=24 | | 100-2n=60 | | -11-2=24 | | 3x-2=4x+6 | | 4x+7=3x+8 | | 3x+x+10=180 | | -6x-4=-64 | | m=21 | | -3x(x-4)-2x(x+3)= | | 2+x=-10 | | -52-3a=8 | | x+2y=27 | | 2x-26=-38+23x | | 16t^2-8t-15=0 | | 4x+7-3x=11 | | x=-3+-1.5Y | | 2x^2+16x+23=0 | | 4t-(5+2t)=37 | | 3x+5y=24 | | 6w+2w=25+47 | | 5(4x+7)-3(5-2x)=98 | | 3x-15=3(x-5) | | x^4=144 | | x-6=-3+9 | | 10-8x=91-29x | | (3x+4)(5x+8)= | | 2x+8+4x-3= | | (4+6)(2+4x)=45-2.5(x+3) |